Development and application of quality assurance and rating software program for power equipment defect texts - LI Yanru; WANG Huifang; CHEN Hao; ZHANG Jiali; JIANG Fan; XIE Yawen (Zhejiang dianli, 2022)
In view of the lack of intelligent tools for the quality assurance and rating of power equipment defect text， the paper proposes a quality assurance and rating software program for power equipment defect text based on standards and historical defects. Firstly， it analyzes the software requirements and determines that the software needs to analyze text quality and automatically rate the defects. Then， according to the characteristics of the two bases， two application processes are designed. Then， the detailed program design process of key functional modules is introduced. The standard-based text quality analysis and automatic defect rating adopt standard tree matching methods. The text quality analysis and automatic defect rating based on history defects adopt graph retrieval methods based on knowledge graph （KG）. Finally， the operation effect of the software is demonstrated by examples. The results show that the software realizes the intelligent quality control and automatic rating of the input defect text by interactive means， which renders powerful support for the closed-loop management of power equipment defects and the improvement of the intelligence level of operation and inspection.